Integrating design and manufacturing for competitive advantage - Susman, Gerald I. (Oxford University Press, 1992)
With more emphasis being placed on the cost and quality of new products and on reducing the lead time to develop them, attention is turning to the increasingly important topic of design for manufacturing (DFM). This involves the collaboration among research and development, manufacturing, and other company functions and is aimed at accelerating the new product development process from product conception to market introduction. A company can create a competitive advantage for itself by managing the process and its related organizational dynamics effectively. This collection of essays focuses on the development of strategic capabilities through use of DFM tools and practices, the role of DFM in specific product development phases, and the social, political, and cultural context within which DFM is introduced.
Keywords: Industrial design.; Engineering design.; New products.; elektronické knihy; electronic books